Deformation Behavior of 2D Composite Cellular Lattices of Ceramic Building Blocks and Epoxy Resin - Eichhorn, Franziska; Keppner, Felix; Köllner, David; Fey, Tobias (Advanced Engineering Materials, 2021)
2D lattice structures with ordered cell designs based on honeycombs are built from modular composites of ceramic building blocks and epoxy resin. The variation of structural parameters as slenderness t2 g−1 and piezoelectric active area q changes the cell design. finite element method (FEM) simulations based on algorithm-generated models within a structural parameter range determine the effect of thermal expansion of different materials (αMaterial) on the mechanical behavior in plane strain mode representative of piezoelectric excitation. The stress distribution σyy and strain amplification ay as a function of deformation are analyzed for Al2O3−PZT and PZT−PZT building block composites. The aim herein is to increase ay by modifying structure design. Furthermore, zero deformation with simultaneously occurring stresses is investigated.
CRIS-Team Scopus Importer:2021-08-27
Keywords: cellular solids; mechanical deformation behaviors; strain amplification; thermal deformation behaviors

Robocasting of alumina hollow filament lattice structures - Schlordt, Tobias; Schwanke, Stanislaus; Keppner, Felix; Fey, Tobias; Travitzky, Nahum; Greil, Peter (Journal of the European Ceramic Society, 2013)
Robotic controlled deposition (robocasting) of an aqueous colloidal alpha-Al2O3 gel for manufacturing of cellular ceramics with periodical lattice structure was investigated. The colloidal gel was loaded with 50 vol% alpha-Al2O3 and exhibits shear-thinning behavior, a shear modulus of 288 kPa and a yield-stress of similar to 700 Pa. Tubular filaments of circular and rectangular cross section having an outer diameter of 1.5 mm and a capillary diameter of 0.75 mm were deposited in an oil bath to fabricate lattice truss structures with free spanning filaments. After freeze drying the robocast grids were sintered in air at 1550 degrees C. X-ray mu-CT revealed continuity of the tubular filaments for long distances (similar to 650 mm). Critical conditions to avoid capillary collapse were discussed by considering bulging stress and pressure distribution within the hollow filament. At short filament length oil infiltration into the capillary driven by capillary suction supports the tubular filament whereas oil flow driven by movement of the tool nozzle causes pressure difference to increase linearly with increasing filament length. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Robocasting; Colloidal gel; Rapid prototyping; Filament based writing; Hollow filaments

Robocasting of alumina lattice truss structures - Schlordt, Tobias; Keppner, Felix; Travitzky, Nahum; Greil, Peter (Journal of Ceramic Science and Technology, 2012)
Robocasting of aqueous colloidal α-AlO gels for manufacturing cellular ceramics with periodical lattice truss structures was investigated. Coagulation of gels loaded with 48 vol% α-Al O was induced by addingCHCOONH. The gels exhibit shear-thinning behavior, shear elastic moduli ranging from 6.7 to 390 kPa and yield-stresses from 25 to 570 Pa. Continuous filaments with a diameter of 0.5mmwere extruded with a deposition speed of up to 35 mm/s on a high-precision six-axis robotic system equipped with a single-screw micro-extruder. The lattice structures consist of alternating layers formed by a linear array of circular rods aligned parallel with a distance of 1mmand an angle of 90° between alternating layers. After being dried for 12 h, the robocast grids were sintered in air at 1650 °C for 2 hresulting in a fractional strut density > 0.95, amean filament diameter of 400 μm, a volume filling fraction of 0.49 (sealed walls) and 0.35 (meshed walls), and macro-cells in the deposition plane of quadratic shape with a mean area of 0.136mm ± 0.017mm Based on gravitation-driven viscous flow, model conditions for attaining free spanning ligaments were discussed. © 2012 Göller Verlag.
Keywords: Alumina gel; Lattice truss structures; Robocasting